Welcome to Sweden - Is the Swedish labour law sufficient to succeed with labour market integration? - Björklund,Michelle (2017)
There are over 65 million people all over the world, fleeing from war and other conflicts. Sweden has become one of the largest residence in Europe for refugees and only in 2015, 163 000 asylum seekers made their way into Sweden. The refugees and asylum seekers in Sweden are struggling to find work and it has been estimated to take approximately 7-10 years to establish themselves on the labour market. This thesis will study how the existing labour law affect refugees and asylum seekers entrance on the labour market. The refugees and asylum seekers legal right to work has been studied in relation to opportunities of actually finding work. International legal framework as well as the Swedish labour regulations has been studied to understand if the Swedish labour law comply with the international legal framework for labour market integration. A long side with Sweden, Germany has been facing similar challenges in order to succeed with labour market integration for refugees and asylum seekers. These countries labour legislation and integration efforts has been compared with each other to answer how their labour legislation differ from each other. The thesis has also been studying if a differentiated legislation can create an issue of discrimination on ethnical grounds.
Keywords: labour law; labour market integration; employment protection; refugees; asylum seekers; right to work; Sweden; Germany.